RPN expressions have stack semantics: a value pushes a number onto the stack, whereas a binary operator pops two values and pushes one back, for a net loss of one element. At the start of an expression the stack is empty, and at the end there is exactly one value – the result.
Now let $V$ be the number of values in the expression, and $B$ be the number of binary operators. Then at the end of the expression, the stack contains $V-B$ values. Since there should be exactly one value remaining, we conclude that $V-B = 1$, or $B = V-1$.
Another way to see this is using structural induction. As you mention, every expression is either a value or is obtained from two expressions combined using a binary operator. Let's prove by induction on the number of values and operators appearing in the expression that $V = B+1$ (in the terminology of the preceding section).
When the expression consists of just a value, $B=0$ and $V=1$, so $V = B+1$. When the expression consists of a binary operator together with two other expressions $E_1,E_2$, we have $V = V(E_1)+V(E_2)$ and $B = B(E_1)+B(E_2)+1$ (I hope the notation is clear). By induction, $V(E_1) = B(E_1)+1$ and $V(E_2) = B(E_2)+1$, so
$$ V = V(E_1) + V(E_2) = B(E_1) + 1 + B(E_2) + 1 = B + 1. $$